2015
DOI: 10.1111/ffe.12327
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue life behaviour of TiAlN and TiAlN/CrN coated notched P20 steel specimens

Abstract: The performance of single layer TiAlN and multilayered TiAlN/CrN physical vapour deposition coatings deposited on AISI P20 steel substrate in affecting overall fatigue resistance of notched specimens was assessed and compared with the performance of the uncoated counterparts. V‐shaped circumferential notches on cylindrical specimens were adopted for fatigue tests. Surface coating characteristics such as hardness, elastic modulus and microstrains were measured and found to be different and often larger than tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…The only exception was one of the specimens with the coating and without the texturing (Figure 3b), where the subsurface inclusion in the material was present and the crack initiated from the inclusion. Nevertheless, due to increased fatigue resistance of the same specimen with the inclusion present on the fractured surface, it could be reasonable to assume that the application of Implementation of the texture on the surface decreases the fatigue life regardless of the coating application or sequence (Figure 2b), which is also consistent with the findings of Rahmat, et al [31] that presence of dimples on the surface confirmed the dimple rupture mechanism in the ductile steel substrate in the coated and uncoated specimens. On the other hand, they [31] investigated notched samples and they found out considerable reductions in fatigue life of the coated notched samples.…”
Section: Fractographic Analysissupporting
confidence: 87%
“…The only exception was one of the specimens with the coating and without the texturing (Figure 3b), where the subsurface inclusion in the material was present and the crack initiated from the inclusion. Nevertheless, due to increased fatigue resistance of the same specimen with the inclusion present on the fractured surface, it could be reasonable to assume that the application of Implementation of the texture on the surface decreases the fatigue life regardless of the coating application or sequence (Figure 2b), which is also consistent with the findings of Rahmat, et al [31] that presence of dimples on the surface confirmed the dimple rupture mechanism in the ductile steel substrate in the coated and uncoated specimens. On the other hand, they [31] investigated notched samples and they found out considerable reductions in fatigue life of the coated notched samples.…”
Section: Fractographic Analysissupporting
confidence: 87%
“…The process of heat treatment involves the use of heating or cooling, usually to extreme temperatures to achieve the wanted result. It is very important manufacturing processes that can not only help manufacturing process but can also improve product, its performance, and its characteristics in many ways [4].…”
Section: Heat Treatmentmentioning
confidence: 99%
“…It is known that the residual stress distributions of the machined surface have significant effects on the service quality of the component, such as the fatigue life, tribological properties and distortion. 1,2 Therefore, it is very important to optimize the distribution of the residual stresses by controlling the cutting parameters.…”
Section: Introductionmentioning
confidence: 99%